Shift Work Disorder and Related Health Problems Among Health Staff in a Hospital - Ismail Ali Shanimar; Asmahasanalial muttalib; Mariam Abdullah Abdulrhim; talalal Hussein khawaji; Aiman Ahmed Wafi; Munirah Hussain Hudani; Laila Ahmed Ahmed Hattani; Maryam Ibrhim Al Wahhas; Alya Fihran Asiri; Hana Mohsen Ali Aloqayli; Ibrahim Ali Yahya Hallush; Maadiah Ahmed Qufayli Assiri (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Shift work is typical for medical staff in hospitals, and working at night and early in the morning disturbs general health conditions. Rapid rotation in shifts has more adverse effects on sleep duration, restlessness, and managing sleep. Mismanaged stress has been responsible for the loss of the ability to perform or increased somatic issues, especially in the case of primary and complementary service staff who suffer not only for patients but also for other staff in the working unit. Due to business necessities and overworking, physicians and nurses working in stabilization clinics and emergency services are exposed to general health problems, stress, exhaustion, anger, disappointment, and self-blame, especially when patients are in life-threatening conditions that exacerbate fatigue. Shift work can lead to work disorder and negative impacts on sleep, monitoring, food intake, competency, emotions, and family activities. Staff working in hospitals may experience parasomnia, impaired mood, headache, weight loss, anxiety, tiredness, premature aging, cardiovascular diseases, diabetes, irritable bowel syndrome, and cognitive disturbances. These health issues are caused by the impairment of internal bio-rhythms characterized as dysfunctional sleep. Shift work also undermines job performance and increases the risk of failure. It is important to recognize and address shift work disorders among health workers. Methods: The study was conducted between May 22nd and 31st, 2019, among healthcare professionals with different characteristics. It consisted of 800 healthcare professionals and 265 non-healthcare professionals. A questionnaire was distributed to the healthcare professionals, with a 100% return rate. The questionnaire asked about the participants' characteristics, work periods, opinions on the effect of different periods on their health, and sleeping habits. Anthropometric measurements were taken by supervised undergraduate students, including weight and height. All procedures were carried out with the hospital's support and within a specific time period. Permission was obtained from the hospital and the Local Ethics Committee. Conclusion: The present study has revealed that long working hours, excessive workload, and other psychological factors contribute to the presence of shift work disorder and related health problems among health staff, including nurses and technicians working alternating shifts. It has also been demonstrated that shift work disorder seriously impacts the staff's daytime cognitive performance and professional lives, including their responsibilities in present work and their career or future. Having an M.D. degree, good family support, and receiving psychological training were found to be important factors for preventing the health staff from having shift work disorder and health problems, as well as helping them alleviate the symptoms of these health problems later. The support and understanding from work peers should also be given important consideration. The present study has demonstrated that between 19.5% and 68.5% of health staff, including nurses and technicians who work in the three nursing units, are shift work disorder sufferers. This result reflects a serious health problem among the staff and also poses a question about the daytime sophistication needed to support the patients, the hospital environment, and the effectiveness of these health staff. Some low-cost interventions, such as ensuring their psychological training at work and providing them with family support, understanding from their work peers, and supportive work shift rostering, might help these health staff in preventing the symptoms of shift work disorder and upholding their ability to function effectively during the day.